ANALISIS PENGGUNAAN CAMPUR KODE DALAM CERAMAH USTADZ DAS'AD LATIF: KAJIAN SOSIOLINGUISTIK - Marsuki, Nurfaika; Widayati, Wahyu; Tobing, Victor Maruli Tua L (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
The purpose of this study is to describe the form of code mixing in Ustadz Das'ad Latif's lectures. The method used in analyzing the data is a qualitative method. The data collection technique in this study used the listening method, the basic technique used tapping techniques, and the follow-up technique, namely SBLC (listening free of engagement). The data analysis technique used is the equivalent method and the basic technique uses the determinant sorting technique (PUP) and the continuation technique uses the equalizing comparison technique. The results of the analysis obtained in this study are in the form of code mixing in Ustadz Das'ad Latif's video lectures in the form of words, phrases, and clauses.